2013
DOI: 10.1002/pssb.201384234
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermal expansion in transversely isotropic space frame trusses

Abstract: The negative thermal expansion (NTE) of a type of space frame structure is investigated herein. On the basis of a space frame structure consisting of tetrahedral representative volume elements, a volumetric thermal strain and a volumetric coefficient of thermal expansion (CTE) models are developed in this paper. The NTE trusses developed herein exhibit a special case of anisotropy known as transverse isotropy. This is achieved by using two types of rod materials, each for the three apex rods and the three base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The first mechanism results in stationary-nodes ( Fig. 1a ) 9 28 29 30 31 33 34 35 , and can be used in an Octet cell to generate thermal expansion isotropy. The second mechanism that we identify here for the first time resorts to stationary-lines that appear in a bi-material tetrahedron upon thermal expansion ( Fig.…”
Section: Mechanisms Of Thermal Deformation In a Tetrahedronmentioning
confidence: 99%
See 3 more Smart Citations
“…The first mechanism results in stationary-nodes ( Fig. 1a ) 9 28 29 30 31 33 34 35 , and can be used in an Octet cell to generate thermal expansion isotropy. The second mechanism that we identify here for the first time resorts to stationary-lines that appear in a bi-material tetrahedron upon thermal expansion ( Fig.…”
Section: Mechanisms Of Thermal Deformation In a Tetrahedronmentioning
confidence: 99%
“…Recent works on mechanical metamaterials have shown that the CTE of periodic materials can be tuned by purposefully designing the architecture of their repeating unit and proper selection of the constituent materials 2 3 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 . It has been shown that low CTE can be obtained through a purely mechanical, and thus temperature-independent, mechanism 3 , which can be in principle designed to make the material operate over a wide range of temperature.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(To remind, NPR, usually denoted as ν αβ in a general case of an anisotropic material, means that when stretched in direction α the material becomes fatter ( not thinner) in direction β (transverse to α ) in which the response is measured.) The remaining six papers concern negative thermal expansion (NTE) , negative stiffness (NS) , ‘negative’ magnetic properties , and graphene .…”
mentioning
confidence: 99%